Woods with Quercus petraea in Tuscany (Italy): a vegetation classification approach - Viciani, Daniele; Gabellini, Antonio; Gennai, Matilde; Foggi, Bruno; Lastrucci, Lorenzo (Mediterranean Botany, 2018)
In Tuscany (Italy), oak mixed woods with high cover values of Quercus petraea are rather infrequent but well documented within local and national phytosociological studies, even if, in the literature, not always analyzed and well characterized from the syntaxonomic view point. We gathered 71 published and unpublished Tuscan phytosociological relevés where Q. petraea was dominant or with relevant cover values, that were investigated by means of multivariate analysis. The ecological requirements of the resulting groups were indirectly calculated by means of Ellenberg Indicator Values (EIV), and the fidelity coefficient (PHI) for the diagnostic species of each group was calculated. According to our analysis, five different types of Q. petraea woods were found to be present in Tuscany. Each group was characterized floristically and ecologically, allowing to investigate their syntaxonomic aspects. Thus we have attributed the Tuscan Q. petraea communities to five different associations, two of which already existing and three are here described as new associations. In the end, some conservation aspects of these woods regarding Natura 2000 habitats are discussed.